Reliability and validity of the Patient Experiences Questionnaire for Interdisciplinary Treatment for Substance Dependence - Continuous Electronic Measurement (PEQ-ITSD - CEM) - Hilde Hestad Iversen; Mona Haugum; Lina Harvold Ellingsen-Dalskau; Oyvind Bjertnaes (BMC, 2024)
Abstract Background Inpatient experiences with interdisciplinary treatment for substance dependence and mental health care are measured using continuous electronic measurements in Norway. Major changes in data collection from cross-sectional surveys to continuous measurements necessitated the revalidation of the instrument. The main purpose of the present study was to determine the psychometric properties of the Patient Experiences Questionnaire for Interdisciplinary Treatment for Substance Dependence - Continuous Electronic Measurement (PEQ-ITSD - CEM). We also aimed to develop a short version of this tool, since completing the original version can be burdensome for some patients. Methods The study included adult inpatients (aged ≥ 16 years) who received substance-dependence treatment at 102 different sections in Norway during 2020-2022 (n = 2,850). Factor structure and item performance were assessed. A short version was developed based on the psychometric testing results that included item response theory analysis. Results The PEQ-ITSD - CEM comprised three empirically based scales with good internal consistency, reliability and validity, which covers treatment and personnel (14 items), milieu (6 items) and outcome (5 items). The results supported a seven-item short version, with three items selected for the treatment and personnel scale, two items for the milieu scale and two items for the outcome scale. Conclusions The PEQ-ITSD - CEM can be recommended for future assessments of patient experiences with interdisciplinary treatment for substance dependence in Norway and in other countries with similar healthcare systems. This short-form version can be applied when respondent burden is a crucial issue.